Rapid injection of near‐inertial shear into the stratified upper ocean at an Antarctic Circumpolar Current front. Issue 9 (7th May 2015) - Forryan, Alexander; Naveira Garabato, Alberto C.; Polzin, Kurt L.; Waterman, Stephanie
Abstract The impact on the upper ocean of the passage of a short, intense storm over a Southern Ocean site, in proximity to an Antarctic Circumpolar Current front, is characterized. The storm causes a wind‐induced deepening of the mixed layer and generates an inertial current. Immediate poststorm observations indicate a mixed layer extending to approximately 50 m depth. Subsequent measurements show the upper ocean to have restratified, injecting near‐inertial shear in stratified waters within 1 day of the storm's passage. This time scale for the development of near‐inertial shear is 1 order of magnitude shorter than that predicted by the β dispersion paradigm. The observed rapid changes in upper ocean stratification point to the existence of an as yet undocumented, efficient mechanism for injection of near‐inertial shear into the stratified ocean that is in turn associated with enhanced turbulence and mixing.